2020
DOI: 10.26508/lsa.201900619
|View full text |Cite
|
Sign up to set email alerts
|

BH4 activates CaMKK2 and rescues the cardiomyopathic phenotype in rodent models of diabetes

Abstract: Diabetic cardiomyopathy (DCM) is a major cause of mortality/morbidity in diabetes mellitus patients. Although tetrahydrobiopterin (BH4) shows therapeutic potential as an endogenous cardiovascular target, its effect on myocardial cells and mitochondria in DCM and the underlying mechanisms remain unknown. Here, we determined the involvement of BH4 deficiency in DCM and the therapeutic potential of BH4 supplementation in a rodent DCM model. We observed a decreased BH4:total biopterin ratio in heart and mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition, it was also shown that BH 4 exerts its beneficial effects in diabetic cardiomyopathy by activating peroxisome proliferator-activated receptor-γ coactivator 1-α (PGC-1α) signaling by interacting with calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2). These effects are also independent of NOS1 activity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also shown that BH 4 exerts its beneficial effects in diabetic cardiomyopathy by activating peroxisome proliferator-activated receptor-γ coactivator 1-α (PGC-1α) signaling by interacting with calcium/calmodulin-dependent protein kinase kinase 2 (CaMKK2). These effects are also independent of NOS1 activity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that in the db/db mouse model lacking BH4, ROS production increases and induces mitochondrial dysfunction. Supplementing BH4 can improve cardiac function, correct myocardial morphological abnormalities, and increase mitochondrial biogenesis by activating the CaMKK2/PGC-1α signaling pathway ( Kim et al, 2020 ). Antioxidant pterostilbene in blueberries regulates AMPK/NRF2/HO-1/PGC-1α signal transduction, which can reduce oxidative stress and inflammation and improve mitochondrial biogenesis in a high glucose rat model ( Kosuru et al, 2018 ).…”
Section: Regulatory Mechanism Of Mitochondrial Dysfunction In Diabeti...mentioning
confidence: 99%
“…Research has demonstrated that diacylglycerol serves as a toxic lipid intermediate in cardiac tissue ( Chokshi et al, 2012 ). The accumulation of ceramide leads to a substantial production of mitochondrial ROS, which induces mitochondrial dysfunction and oxidative stress within myocardial mitochondria ( Law et al, 2018 ; Kim et al, 2020 ). Moreover, the anti-diabetic drug empagliflozin (SGLT2 inhibitor) can lead to a decrease in plasma volume and cardiac preload, regulate superoxide dismutase (SOD) levels and lipid metabolism, reduce oxidative stress, improve mitochondrial function, and thus play a protective effect on the heart ( Kaludercic et al, 2020 ).…”
Section: Regulatory Mechanism Of Mitochondrial Dysfunction In Diabeti...mentioning
confidence: 99%
“…Moreover, tetrahydrobiopterin (BH4), a multifunctional cofactor implicated in regulation of nervous, immune, and cardiovascular systems, is a new potential endogenous activator of CaMKK2. BH4 targets CaMKK2 and promotes recovery of mitochondria in diabetic cardiomyopathy [153].…”
Section: Camkk2mentioning
confidence: 99%